The Global E-commerce Strategy in the Banking Industry: a Comparison of HSBC and Barclays - Xu, Pinqi (2017)
The globalization strategy in banking industry is a niche within the academic discipline of strategy studies. The consequences of E-commerce and technology development of the financial sectors around the world are confronting many business with never before seen challenges. Subsequently, taking part in the ‘go global’ trend has become an inevitable response for many banks, in other words, forcing them to globalization.